2017
DOI: 10.1111/ffe.12736
|View full text |Cite
|
Sign up to set email alerts
|

On Tanaka‐Mura's fatigue crack nucleation model and validation

Abstract: Tanaka‐Mura's fatigue crack nucleation model is revisited. A dimensional problem is found in their cyclic plastic strain formulation obtained by integration of the displacement function, and hence, it is rederived based on the true strain definition. Using the corrected strain formulation, a new fatigue crack nucleation life expression is obtained, and for the first time, low cycle fatigue lives of several metals and alloys are predicted without resorting to experiments. With such theoretical life as the basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…As implied by Equation (10), even application of a single stress component may induce dislocation distributions of all modes, depending on the coupling terms in the F matrix. In the previous paper, 6 the author showed that the isotropic formulation can satisfactorily predict the low-cycle fatigue life of polycrystalline materials with appreciable plastic deformation. In this sense, metal fatigue is almost unavoidable under repeated loading of any kind exceeding the lattice frictional resistance t i F .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As implied by Equation (10), even application of a single stress component may induce dislocation distributions of all modes, depending on the coupling terms in the F matrix. In the previous paper, 6 the author showed that the isotropic formulation can satisfactorily predict the low-cycle fatigue life of polycrystalline materials with appreciable plastic deformation. In this sense, metal fatigue is almost unavoidable under repeated loading of any kind exceeding the lattice frictional resistance t i F .…”
Section: Discussionmentioning
confidence: 99%
“…In the previous paper, 6 the author showed that the isotropic formulation can satisfactorily predict the low-cycle fatigue life of polycrystalline materials with appreciable plastic deformation. Using the surface energy value of 2.3729 J/ m 2 and Burgers vector of 2.48 × 10 −10 m for pure iron, 6 and the Young's modulus of the orientation (for simple estimation of the single mode II crack nucleation, it is assumed that the F matrix takes the "isotropic" form but with the directional modulus, as reasoned from Ting 13 ), Equation (23) then predicts the fatigue crack nucleation life (applying the same surface roughness factor as in Wu 6 ) is calculated to be 35 963 cycles. Then, only a few dislocation pile-ups exist in the most favorable slip systems, depending on the microstructure, while the rest of the body remains elastic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations